Prevalence and determinants of low testosterone levels in men with type 2 diabetes mellitus; a case-control study in a district hospital in Ghana. - Dorcas Serwaa; Folasade Adenike Bello; Kayode O Osungbade; Charles Nkansah; Felix Osei-Boakye; Samuel Kwasi Appiah; Maxwell Hubert Antwi; Mark Danquah; Tonnies Abeku Buckman; Ernest Owusu (Public Library of Science (PLoS), 2021)
Diabetes mellitus, an endocrine disorder, has been implicated in many including hypogonadism in men. Given the fact that diabetes mellitus is becoming a fast-growing epidemic and the morbidity associated with it is more disabling than the disease itself. This study sought to assess the prevalence of low testosterone levels and predictors in type 2 diabetes mellitus patients and non-diabetic men in a district hospital in Ghana. This hospital-based case-control study comprised 150 type 2 diabetics and 150 healthy men. A pre-structured questionnaire and patient case notes were used to document relevant demographic and clinical information. Venous blood sample of about 6 ml was taken to measure FBS, HbA1c, FSH, LH, and testosterone levels. All data were analyzed using STATA version 12 (STATA Corporation, Texas, USA). The overall hypogonadism in the study population was 48% (144/300). The prevalence of hypogonadism in type 2 diabetic subjects was almost three times more than in healthy men (70.7% vs 25.3%). The odds of having hypogonadism was lower in the men with normal weight and overweight with their underweight counterparts (AOR = 0.33, 95% CI; 0.12-0.96, p = 0.042) and (AOR = 0.29, 95% CI; 0.10-0.84, p = 0.023) respectively. Also, the odds of suffering from hypogonadism was lower in non-smokers compared with smokers (AOR: 0.16, 95% CI; 0.05-0.58, p = 0.005). Participants who were engaged in light (AOR: 0.29, 95% CI; 0.14-0.61, p = 0.001), moderate (AOR: 0.26, 95% CI; 0.13-0.54, p<0.001) and heavy (AOR: 0.25, 95% CI; 0.10-0.67, p = 0.006) leisure time activities had lower odds hypogonadal compared to those engaged in sedentary living. Type 2 diabetic men have high incidence of hypogonadism, irrespective of their baseline clinical, lifestyle or demographic characteristics. Smoking and sedentary lifestyle and BMI were associated with hypogonadism in the study population. Routine testosterone assessment and replacement therapy for high risk patients is recommended to prevent the detrimental effect of hypogonadism in diabetic men.